Cross-sectional echocardiographic diagnosis of systemic venous return. Issue 4 (October 1982) - Huhta, J C; Smallhorn, J F; Macartney, F J; Anderson, R H; de Leval, M
Abstract : To determine the sensitivity and specificity of cross-sectional echocardiography in diagnosing anomalous systemic venous return we used the technique in 800 consecutive children with congenital heart disease and whom the diagnosis was ultimately confirmed by angiography. Cross-sectional echocardiography was performed without prior knowledge of the diagnosis in all but 11 patients, who were recalled because of a known abnormality of atrial situs. The sensitivity of cross-sectional echocardiographic detection of various structures was as follows: right superior vena cava 792/792 (100%); left superior vena cava 46/48 (96%); bilateral superior vena cava 38/40 (95%); bridging innominate vein with bilateral superior vena cava 13/18 (72%); connection of superior caval segment to heart (coronary sinus or either atrium) (100%); absence of suprarenal inferior vena cava 23/23 (100%); azygos continuation of the inferior vena cava 31/33 (91%); downstream connection of azygos continuation, once seen, 21/21 (100%); partial anomalous hepatic venous connection (one hepatic vein not connected to the inferior vena cava) 1/1 (100%); total anomalous hepatic venous connection (invariably associated with left isomerism) 23/23 (100%). The specificity of each above diagnoses was 100% except in one infant with exomphalos in whom absence of the suprarenal inferior vena cava was incorrectly diagnosed. Thus cross-sectional echocardiography is an extremely specific and highly sensitive method of recognizing anomalous systemic venous return. It is therefore of great value of planning both cardiac catheterisation and cannulation for open heart surgery.